Metamorphic response to Alpine thrusting of a Crustal-scale basement nappe in southern Calabria (Italy) - Brandt, Sönke; Schenk, Volker (Journal of petrology, 2020)
Structural, geophysical and age data indicate that the tilted cross-section of the Variscan continental crust exposed in the Serre of southern Calabria forms the uppermost Alpine nappe (‘Serre nappe’) of three Variscan basement slices derived from the southern European margin. This Alpine nappe stack is a fragment of the western Mediterranean Alps and rests now, after Miocene emplacement, on top of the Apennine carbonate platform. We report for the first time a P-T path for prograde Alpine metamorphism, which is restricted to the two lower nappes (Castagna and Bagni nappes) that are squeezed between cooler tectonic units, the Serre nappe above and the Apennine platform below. Therefore, we attribute their metamorphism to tectonic loading and concomitant shear heating during Eocene south-directed overthrusting of the crustal-scale Serre nappe. In the underlying Castagna nappe, Alpine metamorphism is only locally recorded, mainly by new growth of garnet, forming at the expense of retrogressed Variscan biotite dated at 43 Ma. The local existence of Alpine besides relict Variscan mineral assemblages in the strongly but heterogeneously overprinted rocks allows for characterization of metamorphic evolutions during both the Alpine and Variscan orogeneses in the former intermediate level of the Variscan crust of Calabria. The metamorphic evolutions have been reconstructed through P-T pseudosection modelling for Al-rich metasediments. In the Castagna nappe, rarely preserved Variscan garnet-sillimanite-biotite-ilmenite-plagioclase-quartz (± K-feldspar ± Si-poor white mica) assemblages formed under amphibolite-facies subsolidus conditions (650 ± 60 °C, 4·0 ± 0·5 kbar). During subsequent decompression and cooling to greenschist-facies conditions garnet was replaced by biotite-sillimanite and later by white mica-chlorite intergrowths. Retrogression of Variscan biotite is evidenced by the exsolution of ilmenite along grain boundaries and cleavages, textures that were subsequently overgrown by Alpine garnet coexisting with Si-rich white mica, rare chloritoid (in metapelites), and hornblende (in metagreywackes). Alpine garnet shows prograde zoning and is Ca-rich, and thus is distinct from unzoned and Ca-poor Variscan garnet porphyroblasts. Estimated conditions (520 ± 40 °C, 8·0 ± 1·0 kbar) record elevated pressures during Alpine lower amphibolite-facies metamorphism. In the lowermost Bagni nappe, rare prograde-zoned, Ca-rich garnet in strongly retrogressed mylonitic quartz-phyllites allows isopleth thermobarometry, which indicates lower amphibolite-facies conditions (555 ± 10 °C, 7·4 ± 0·3 kbar) resembling those for Alpine garnet growth in the Castagna nappe. The similar clockwise P-T paths for prograde Alpine metamorphism and the consistent peak pressures of 7-9 kbar in the Castagna and Bagni nappes point to a joint short-lived metamorphism during overthrusting of the crustal-scale Serre nappe within the south European margin during the north-directed subduction of the Alpine Tethys. South-directed overthrusting of the now tilted Variscan crustal section of the Serre along the up to 500 m thick mylonite horizon of the Curinga-Girifalco Line is in agreement with seismic data indicating an extended, few kilometres thick low-velocity zone (Bagni and Castagna nappes and mylonites of the Curinga-Girifalco Line) below the exposed lower crustal section of the Serre nappe. Alpine tectonic transport direction, timing and metamorphic conditions described here are consistent with those reported from the Aspromonte area in southernmost Calabria, suggesting a coeval Alpine history characterized by metamorphism owing to nappe loading and concomitant shear heating. The Alpine subduction-erosion-accretion processes inferred here for the Calabrian basement nappes resemble those proposed for the Dent Blanche nappe system in the Western Alps.